Application of Virtual Reality and Augmented Reality in the Performance Management Process and Productivity: A Systematic Review - Valente, Maria Marques; Carneiro, Andreia; Torres, Manuela; Figueiredo, Clara; Santos, Mariana; Correira, Tiago; Seixas, Daniela; Lopes, Liliana; Costa, Daniel; Silva, Mariana; Meirinhos, Viviana; Ferreira, Pedro; et al. (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
The job market has been in continuous development. Both depleting resources due to rapid adaptation and reaching higher effectiveness and reducing costs. This is also reflected in the need for the companies to guarantee support mechanisms capable of enhancing the quality and productivity of their employees in order to facilitate the processes of learning and task development. Thus, the technologies of Virual Reality and Augmented Reality are slowly finding their way into all areas of business, including in Human Resources (HR) as an important tool to follow the technological progress towards the improvement of productivity (Holm, Danielsson, Syberfeldt, Moore, & Wang, 2017)Such technologies can have a great impact in the development of new skills, revolutionizing the way companies provide their employees with learning experiences which help them to acquire knowledge and skills, better achieving performance goals. Currently, there is not a single organization that can survive without well-trained memberslification of complex processes, Thus, in comparison to traditional methods, the use of VR and RA has shown benefits in terms of improved safety and performance and, increased productivity (Patle, Manca, Nazir, & Sharma, 2018).